Contemporary world cultures - Chu, Gregory H.; Hardwick, Susan Wiley; Holtgrieve, Don (Pearson, 2016)
North America -- Central America and the Caribbean -- South America -- Europe -- Russia, Central Asia, and the Caucasus -- North Africa and Southwest Asia -- Sub-Saharan Africa -- South Asia -- East Asia -- Southeast Asia -- Australia and the Pacific -- United States Constitution -- Primary sources -- Declaration of Independence -- 21st century skills -- Atlas -- Glossary